좌측 주기관지 피덩이를 우로키나아제 기관내 국소주입으로 제거한 1예 - 최정; 이사라; 곽충환; 배현혜; Choi, Jung; Lee, Sa Ra; Kwak, Choong Hwan; Pae, Hyun Hye (Tuberculosis and respiratory diseases, 2003)
Background : Airway obstruction due to blood clot occurs unusually but in a variety of clinical settings. Initial efforts for removal of the endobronchial blood clot involve flexible bronchoscopic evaluation with saline lavage and suctioning and then forceps extraction. If unsuccessful, further options include rigid bronchoscopy, Fogarty catheter dislogement of the clot, and topical thrombolytic agents. The several successful uses of endobronchial streptokinase or urokinase to dissolve an endobronchial blood clot have been previously reported, but not yet in Korea. Herein we describe a 51-year old man with superior vena cava thrombosis secondary to Behcet's disease who experienced life threatening airway obstruction after hemoptysis due to a large organized blood clot in left main bronchus. Urokinase(260,000 U), injected through a fiberoptic bronchoscope, totally dissolved the clot. No complications occurred. 저자들은 좌주기관지내 피덩이로 인해 폐허탈과 심한 호흡부전을 보인 환자에서 기관지내 국소 우로키나아제의 사용으로 피덩이를 효과적으로 제거한 예를 경험하였기에 보고하는 바이다.